Chronic Progressive External Ophthalmoplegia (CPEO): Rehabilitation utilizing scleral contact lenses - Nir Erdinest; Nadav Shemesh; Naomi London; David Landau; Itay Lavy (American Journal of Ophthalmology Case Reports)
Purpose: To evaluate the use of scleral contact lenses in managing symptoms of Chronic Progressive External Ophthalmoplegia (CPEO) after failed conventional treatments. Observations: A 69-year-old female with CPEO presented with persistent discomfort and blurry vision despite artificial tears and ointment treatments. Diagnosed with blepharoptosis, myogenic ptosis, dry eye syndrome, dermatochalasis, and lagophthalmos, she showed no improvement post-prolene frontalis suspension surgery. Scleral lenses provided immediate ptosis relief, improving spectacle-corrected visual acuity from 6/12 (−3) and 6/15 (−2) to 6/6 (−1) and 6/7.5 (−2) in the right and left eyes, respectively. Prior to scleral lens fitting, ocular surface staining showed an Oxford score of 3.0 in both eyes, which improved to <1 and remained stable through the four-year follow-up. The OSDI score decreased from 95.83 to 4.17, with sustained symptom relief and stable visual clarity reported throughout, without complications. Conclusions and importance: Scleral contact lenses provided significant relief from ptosis, markedly improved visual acuity, substantially reduced ocular surface damage, and nearly eliminated subjective dry eye symptoms in this complex CPEO case. These lenses are recommended as a primary therapeutic option for CPEO patients with ocular surface complications when conventional treatments are ineffective, offering sustained symptom relief and enhanced visual function.